Managing the rabble with dignity and respect - Richie, Matt (Journal of crime and justice, 2021)
Individuals incarcerated in America’s jails face a number of barriers (substance and alcohol abuse, mental health issues, physical ailments, homelessness). The nature of jail stays makes it difficult to treat or support individuals plagued by these issues. As such, correctional officers are charged with managing these individuals. By conducting in-depth interviews with correctional officers, this study answers the question of how these individuals manage an ever-changing population with a host of problems by interviewing correctional officers. Results suggest that interpersonal communication skills are the primary way officers obtain compliance from incarcerated individuals. By treating the rabble class with dignity and respect, officers not only avoid physical confrontations but can also provide support for these individuals. Policy implications are also discussed.